How 'Madsen' has shaped Pacific Northwest wheat and beyond. Issue 3 (19th May 2020) - Carter, A. H.; Allan, R. E.; Shelton, G. B.; Burke, A. B.; Balow, K. A.; Hagemeyer, K. E.; Chen, X. M.; Engle, D.; Garland‐Campbell, K. A.; Morris, C. F.; Murray, T. D.; Paulitz, T.; et al.
Abstract: It is never known how well new cultivars will perform under commercial production until they are released and grown across different environments. Every cultivar released has a different impact on the region for which it was intended. Some cultivars are in commercial production for only a few years, whereas others are cultivated for decades. 'Madsen', a soft white winter wheat released in 1988 for production in the Pacific Northwest (PNW), has been in commercial production for 30 years. Once the dominant cultivar grown in the PNW, Madsen was produced mainly because of its high yield potential and excellent biotic stress resistance. Currently, Madsen is grown on limited hectares, replaced by many cultivars with higher yield potential; yet its legacy has gone far beyond commercial production. Madsen has been the parent of over 45 released cultivars, many of which were the lines that replaced it in commercial production. It is used as a parent mainly because of its excellent disease resistance to common diseases of the PNW. Madsen has also been used in research projects to identify disease resistance genes. In some cases Madsen was found to be carrying resistance genes the breeder was not aware of but were discovered later in research or field screenings. In this paper, we review the history of Madsen to determine what made it such a successful cultivar and parental line. Data were collected from multiple field trials and research papers and summarized for review.